Association between neutrophil-to-high-density lipoprotein cholesterol ratio (NHR) and psoriasis risk: a nationally representative cross-sectional study - Liang, Huazheng; Si, Wenyue; Huang, Huilan; Li, Lin; Li, Xin; Yang, Kaiying (Frontiers in Immunology, 2025)
ObjectiveTo investigate the association between the neutrophil-to-high-density lipoprotein cholesterol ratio (NHR) and the risk of psoriasis.MethodsThis cross-sectional study analyzed data from the National Health and Nutrition Examination Survey (NHANES) for the periods 2003–2006 and 2009–2014, including 21,723 adults aged ≥20 years. Weighted multivariable logistic regression models were used to examine the association between NHR and psoriasis, with stepwise adjustments for demographic, metabolic parameters, and comorbid factors. Subgroup analyses, sensitivity analyses and smoothed curve fitting were conducted to assess the robustness and potential nonlinearity of the association.ResultsThe prevalence of psoriasis was 2.75%. Multivariable regression revealed a significant positive association between elevated NHR levels and psoriasis risk (unadjusted model: OR = 1.11, 95% CI = 1.06–1.16, p < 0.001; fully adjusted model: OR = 1.08, 95% CI = 1.02–1.14, p = 0.007). Participants in the highest NHR quartile (Q4) exhibited a 63% higher risk of psoriasis compared to those in the lowest quartile Q1 (OR = 1.63, 95% CI = 1.27–2.08, p < 0.001). Subgroup analyses demonstrated consistent associations across most strata, although the relationship was significantly modified by alcohol consumption history (p for interaction = 0.048). The sensitivity analyses substantiate NHR as a temporally stable and confounder-independent biomarker for psoriasis risk, as evidenced by consistent effect estimates across multiple analytical models and population strata.ConclusionHigher NHR levels are independently associated with an increased risk of psoriasis. Further prospective cohort studies and mechanistic experiments are needed to validate its predictive performance and potential role in psoriasis risk stratification and monitoring.